Alkyltin clusters: the less symmetric Keggin isomers. Issue 29 (11th July 2018) - Hutchison, Danielle C.; Stern, Rebecca D.; Olsen, Morgan R.; Zakharov, Lev N.; Persson, Kristin A.; Nyman, May
Abstract : Sn 4+ forms the only Keggin ion family that favors the lowest symmetry β and γ isomers. Abstract : The Keggin structure is prevalent in nature and synthesis, self-assembled from many metals across the periodic table as both isolated clusters and building blocks of condensed framework oxides. Here we present a one-step synthesis to obtain the sodium-centered butyltin Keggin ion in high yield and high purity, important for mechanistic nanolithography studies. Extensive solution characterization (small-angle X-ray scattering, 1 H, 13 C and 119 Sn nuclear magnetic resonance, electrospray mass spectrometry) also confirms solutions contain only the Na-centered dodecamers. We report three butyltin Keggin structures: the β-isomer (β-NaSn12 ), the γ-isomer (γ-NaSn12 ), and a γ-isomer capped with an additional butyltin (γ-NaSn13 ). All Keggin ions presented here have the general formula [NaO4 BuSn12 (OCH3 )12 (O, OH)12 ] (Bu = butyl), and are of neutral charge. The lack of counterions (OH − ) facilitates mechanistic lithographic studies without inference from hydrolysis chemistry. The methanol reaction media enables solubility and ligates the cluster, both important to obtain high purity materials. Despite the monospecific nature of the NaSn12 solutions, NMR reveals both isomer interconversion and ligand exchange. DFT computational comparisons of our three isolated structures, the capped β-isomer (β-NaSn13 ), along with hypothetical α-isomers (α-NaSn12 and α-NaSn13 ), showed that the stability ranks β-NaSn12 > γ-NaSn12 > α-NaSn12, consistent with experimental observation. The uncapped isomers were computationally determined to be more stable than the respective capped analogues. These clusters provide a unique opportunity to investigate the lower-symmetry Keggin isomers, and to determine structural factors that control isomer selectivity as well as isomer labilization.